1996
DOI: 10.1002/bbpc.19961000619
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of complexation of heavy metal ions with polyelectrolytes in aqueous solution

Abstract: The kinetics of the binding of Ni2+ to polycarboxylate anions have been studied using pressure‐ and temperature‐jump relaxation techniques. The reaction proceeds via the two‐step Eigen mechanisms: free ions form the outer‐sphere and in the second step the inner‐sphere complex. The outer‐sphere complex is exceptionally stable due to the polyelectrolyte effect, and the electrical potential at the polyelectrolyte surface is estimated to be ψ ≈−86 mV. The rate constant for the formation of the inner‐sphere complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In an analogous manner, it is also possible to take into account the binding of metal ions on functional groups of polyelectrolytes [17,18]. Employing a kinetic approach, we could successfully model the mechanism of reaction of Ni 2+ and Al 3+ with polycarboxylates via the classical two-step mechanism for metal ion complexation [19,20]. In the first step, outer-sphere complexes are formed by electrostatic attraction, where one hydration shell separates the metal ions from the functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…In an analogous manner, it is also possible to take into account the binding of metal ions on functional groups of polyelectrolytes [17,18]. Employing a kinetic approach, we could successfully model the mechanism of reaction of Ni 2+ and Al 3+ with polycarboxylates via the classical two-step mechanism for metal ion complexation [19,20]. In the first step, outer-sphere complexes are formed by electrostatic attraction, where one hydration shell separates the metal ions from the functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case with with the formation of NT A complexes of Al3+, where the rate constant, k34 = 0.27 S·l. is nearly tentimes smaller than k23 (Pohlmeier and Knoche 1996).…”
Section: Kinetics and Mechanism Of Complexationmentioning
confidence: 93%
“…Relaxation times in the range of 0.2-1 ms were observed at 25 °C. 2 It has been assumed that protonation of the carboxylic groups proceeds much faster, since the protons are not involved in internal hydrogen bridges and thus the reaction should occur with diffusion-controlled speed. 3 However, it has been shown already in 1972 by Weiss et al 4 that at pH = 7 protonation may be relatively slow for polycarboxylic acids, and it may be necessary to take into account the rate of protonation when discussing the kinetics of nickel-complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…For the understanding of the mechansim of this process, additional kinetic measurements must be performed, and in a previous study we reported on the kinetics of nickel-complex formation of a polycarboxylic acid in nearly neutral solutions (pH ∼ 6). Relaxation times in the range of 0.2−1 ms were observed at 25 °C . It has been assumed that protonation of the carboxylic groups proceeds much faster, since the protons are not involved in internal hydrogen bridges and thus the reaction should occur with diffusion-controlled speed .…”
Section: Introductionmentioning
confidence: 99%